Migration Processes and Localization, Uzbekization Policy in Uzbekistan (1925-1933 Yеars) - Shaira Shadavlatovna Davlatova (International Journal on Integrated Education, 2022)
In this article, the ideas about the policy of colonization carried out by the Soviet authorities in Uzbekistan, its impact on representatives of the local nationality, false localization and uzbekization policy implemented in the whole country, including in the Surkhandarya district, as a result of migration processes are expressed.